2022
DOI: 10.1101/2022.10.21.513154
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Structural and functional analysis of YopR and identification of an additional key component of the SPβ phage lysis-lysogeny management system

Abstract: Prophages need to tightly control their lifestyle to either be maintained within the host genome or enter the lytic cycle. The SPβ prophage present in the genome ofBacillus subtilis168 was recently shown to possess anarbitriumsystem defining its replication stage. Using an historicB. subtilisstrain harboring the heat-sensitive SPβ c2 mutant, we analyzed a key component of the lysis-lysogeny decision system called YopR, which is crucial for maintenance of lysogeny. Here, we demonstrate that the heat-sensitive S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 89 publications
0
2
0
Order By: Relevance
“…The prophage SPβ contains the open reading frame for blyA , which plays a crucial role in the lytic activity of the phage in the host cell . SPβ integrates into the genome of its bacterial host and has been found to be ubiquitous in B. subtilis 168. , SPβ is a lysogenic phage with a temperature-dependent lytic life cycle in B. subtilis 168. ,, Previous studies have demonstrated that the level of expression of blyA in B. subtilis 168 increases at high temperatures, and its heat-induced expression is necessary for the lysis of the host cell . Although it is known that heat stress induces the expression of blyA and the proliferation of the SPβ prophage in B. subtilis 168, the underlying molecular mechanism that drives this process has yet to be elucidated.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The prophage SPβ contains the open reading frame for blyA , which plays a crucial role in the lytic activity of the phage in the host cell . SPβ integrates into the genome of its bacterial host and has been found to be ubiquitous in B. subtilis 168. , SPβ is a lysogenic phage with a temperature-dependent lytic life cycle in B. subtilis 168. ,, Previous studies have demonstrated that the level of expression of blyA in B. subtilis 168 increases at high temperatures, and its heat-induced expression is necessary for the lysis of the host cell . Although it is known that heat stress induces the expression of blyA and the proliferation of the SPβ prophage in B. subtilis 168, the underlying molecular mechanism that drives this process has yet to be elucidated.…”
mentioning
confidence: 99%
“… 11 , 12 SPβ is a lysogenic phage with a temperature-dependent lytic life cycle in B. subtilis 168. 10 , 13 , 14 Previous studies have demonstrated that the level of expression of blyA in B. subtilis 168 increases at high temperatures, and its heat-induced expression is necessary for the lysis of the host cell. 10 Although it is known that heat stress induces the expression of blyA and the proliferation of the SPβ prophage in B. subtilis 168, 10 the underlying molecular mechanism that drives this process has yet to be elucidated.…”
mentioning
confidence: 99%